Lameness in cattle 2. Managing claw health through appropriate trimming techniques. Issue 5 (7th May 2015) - Mahendran, Sophie; Bell, Nick
Abstract : Bovine lameness is a major challenge facing the dairy industry, with negative impacts on milk production, fertility and longevity of animals. Our understanding of the aetiopathogenesis of claw horn lesions has evolved, leading to alterations in the way we approach routine claw trimming, such as the number and timings of foot inspections. While there have been few changes to the basic principles of trimming that were first described by Toussaint Raven (1985), it is now clearly recognised that application of poor and inappropriate techniques can cause iatrogenic lameness. This article, the second in a two‐part series on lameness, reviews the evidence and rationale of claw trimming techniques, for the management of claw horn health in dairy cows and heifers. The first article (Maxwell and others 2015) discussed recent research on lameness.